2011
DOI: 10.1007/s10311-011-0325-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for DNA-diquat interaction and cytotoxicity in in vitro rat cells

Abstract: Over 98% of sprayed insecticides and 95% of herbicides reach non-target species in air, soil, and water. Numerous studies have reported that pesticide residues can cause acute and chronic toxicity. Pesticide residues can be carcinogenic, mutagenic, and immunotoxic. There are actually too few studies that bridge the disciplines of chemobioanalysis and environmental toxicology. Here, we assessed the cytotoxicity of a bipyridilium herbicide diquat in rat adrenal pheochromocytoma cells (PC12). Our results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…DNA is quite often the main molecular target of chemicals, and many forms of cancer could be partly due to acute changes in DNA functions caused by harmful small molecules. Many studies regarding the interactions between DNA and harmful chemicals have been reported, such as pyriproxyfen [9], permethrin [10], clodinafoppropargyl [11], diquat [12], salbutamol [13], ractopamine [14], and heavy metal ions [15]. In recent years, some food additives such as dyes [16][17][18] and sweeteners [19,20] bound to DNA were also investigated.…”
Section: Introductionmentioning
confidence: 98%
“…DNA is quite often the main molecular target of chemicals, and many forms of cancer could be partly due to acute changes in DNA functions caused by harmful small molecules. Many studies regarding the interactions between DNA and harmful chemicals have been reported, such as pyriproxyfen [9], permethrin [10], clodinafoppropargyl [11], diquat [12], salbutamol [13], ractopamine [14], and heavy metal ions [15]. In recent years, some food additives such as dyes [16][17][18] and sweeteners [19,20] bound to DNA were also investigated.…”
Section: Introductionmentioning
confidence: 98%
“…[13,14,17] Figure 10 shows the changes in fluorescence emmision spectra for compound L4 during titration with ct-DNA.O nly for diquats L3 and L4 was it possible to apply aS tern-Volmer relationship;t he value of the corresponding constant (K SV )w as higher for compound L3 (4.25 10 3 m À1 )t han for L4 (3.38 10 3 m À1 ), which can be attributed to the planarity of ligand L3 (Table 1). In all cases, an increase in absorption was observed between 200 and 300 nm owing to the intrinsic DNA absorbance in this region.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular orbital calculations can be used to estimate 13 CNMR chemical shifts. Ab initio and DFT calculations of NMR shieldinga tv ery accurate levels of approximation are available in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations